Lamellar pathology in horses with pituitary pars intermedia dysfunction. (4th June 2015) - Karikoski, N. P.; Patterson‐Kane, J. C.; Singer, E. R.; McFarlane, D.; McGowan, C. M.
Summary: Reasons for performing study: Hoof lamellar pathology in horses with pituitary pars intermedia dysfunction (PPID) has not been described previously. Objectives: To describe the histomorphometry and pathological lesions in hoof lamellar tissue of animals that had PPID with or without concurrent laminitis, with reference to age‐matched controls. We hypothesised that lamellar lesions consistent with laminitis would be associated with PPID, even in animals without current or historical laminitis. Study design: Prospective case–control study. Methods: Mid‐dorsal hoof histological sections were obtained post mortem from the forelimbs of 16 PPID‐affected animals either with (n = 6) or without laminitis (n = 10) and 10 age‐ and breed‐matched controls. Sections were examined by a blinded veterinary pathologist. The length and width of 10 primary epidermal lamellae were measured using image analysis software. The morphology and pathology of primary and secondary epidermal lamellae were then typed or graded in axial, middle and abaxial regions. Fasting serum insulin, plasma adrenocorticotropin and blood glucose concentration were measured from blood samples taken prior to euthanasia. Results: All animals with PPID and laminitis had fasting hyperinsulinaemia (median 74.1 miu/l, interquartile range 49.9–349.5 miu/l) whereas PPID animals without laminitis had serum insulin concentrations below the upper limit of the reference range (<20 miu/l). Lamellar pathology in PPID animals with laminitis was variable in severity and unrelated to the reported duration of laminitis (range 2 months–5 years). Most lesions were located abaxially within the lamellar tissue and included increased length and width of the lamellae, chronic abnormal keratinisation, interlamellar epidermal bridging and cell death with more acute lamellar tearing in some cases. The lamellae of PPID animals without laminitis were normal referent to the relevant control group. Conclusions: Whether PPID and hyperinsulinaemia have a causal inter‐relationship or not, it may only be the hyperinsulinaemia that is associated with lamellar morphological alteration and pathology consistent with laminitis.